Human population genetics - Relethford, John (Foundations of human biology, 2012)
"Human Population Genetics will provide an introduction to mathematical population genetics, along with relevant examples from human (and some non-human primate) populations, and will also present concepts and methods of population genetics that are specific to the study of human populations. The purpose of this book is to provide a basic background text for advanced undergraduate and graduate students interesting in the mechanisms of human microevolution"--